PENGARUH PENERAPAN MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V SD NEGERI MACCINI 2 KOTA MAKASSAR - Annisa; Rahmawati Patta; Hamzah Pagarra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to (1) know the description of the application of quantum learning learning models in mathematics (2) know the description of students' critical thinking skills, and (3) knowing the effect of the application of the quantum learning learning model on the critical thinking skills of students in the class of class V mathematics subjects SD Negeri Maccini 2 Makassar City. The approach in this study is quantitative with the type of quasi experimental design with pretest-posttest control group design. The population and sample in this study were all grade students of Maccini 2 SD Negeri Makassar City with a total of 50 students based on saturated sampling techniques. The data in this study were collected using documentation, observation sheets and objective tests given before and after the implementation of learning. Data analysis techniques use descriptive statistical analysis and inferential statistical analysis. The results of descriptive analysis show that the application of the Quantum Learning learning model at Meeting I was running effectively and at the meeting II was very effective. The results of inferential analysis using the Independent Sample T-Test show that there are differences in posttest results between the experimental class and the control class. This shows that there is an increase in critical thinking skills of mathematics students in the experimental group. so it can be concluded that: (1) The learning process by applying the Quantum Learning learning model takes place very well, (2) Student test results show an increase in the critical thinking ability of students in mathematics in learning, (3) there is a significant influence on the application of the Quantum learning model Learning on the critical thinking skills of Mathematics students in class V SD Negeri Maccini 2 Makassar City.